Knowledge of newborns’ mothers on breastfeeding during covid-19, hiv and tuberculosis infection attendee in selected hospitals - Akther, Salma; Akhtar, Khursheda; Shawan, Esrat Zahan (Journal of Preventive and Social Medicine, 2024)
Background: Two-thirds of the HIV mothers planned to breastfeed their infants while one-third opted for formula feeding; same as during Tuberculosis or COVID-19 infection. What would be the mother do during breastfeeding? Whether the mother could breastfeed their newborn or not. For that it is necessary to assess the level of knowledge of newborns mother on breastfeeding during COVID-19, HIV and Tuberculosis. Methods: It was a descriptive type of cross sectional study was conducted at Maternal and Child Health Training Institute, Azimpur, Dhaka from 1st January to 31st December 2021. Mother of newborns who are willing to participate were conveniently selected. Around 289 sample was selected. Pre tested semi structured questionnaire was used to collect the data. Level of knowledge was measured by knowledge score. Each question of knowledge carries one (01) mark. Each correct answer had 1 mark and incorrect answer had 0 mark. 1-11 score (<60%) was categorized as fair knowledge; 12-15 score (60-79%) was categorized as good knowledge and 16-20% score (80% and above) had very good knowledge. Results: Age and knowledge of whether TB-positive mothers may breastfeed have an association (2=4.488, p = 0.034); age and knowledge of whether HIV-positive mothers can breastfeed have an association (2=9.632, p = 0.002). There is a correlation between occupation and knowledge of whether mothers who have COVID 19 positive status can breastfeed (5.044; p=0.046), as well as a correlation between occupation and knowledge of whether mothers who have TB positive status (9.365; p=0.002). Family income has a correlation with knowledge of whether mothers who are COVID 19 positive, HIV positive, or TB positive can breastfeed (2=17.695, p = 0.0001), COVID 19 positive mothers have a correlation with knowledge of whether they can breastfeed (2=7.511, p = 0.006), and HIV positive mothers have a correlation with knowledge of whether they can breastfeed (2=8.675, p = 0.003). Education level and awareness of whether COVID 19 positive mothers can breastfeed are correlated (2=10.315, p = 0.001), as are knowledge of whether TB positive mothers can breastfeed (2=10.880, p = 0.001). Conclusion: Develop targeted educational programs for mothers based on their demographic characteristics, such as age, occupation, and education level. JOPSOM 2023; 42(1):40-47